PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN DIVISI SDM&UMUM DAN DIVISI OPERASIONAL DI PT PJB UP GRESIK) - NUR INDAHSARI, VELLY (Jurnal Ilmu Manajemen (JIM), 2017)
The development of the times and the increasingly sophisticated technology makes business competition is getting tight and firm as an organization that produces good products in the form of goods or services is in need of resources for the activities of the operations. Humans as one physical resources plays a role in determining all existing activities are concerned with. PT PJB UP Gresik is one generation unit that belongs to PT PJB are engaged in business activities of the electric power provider in the form of electric power generation activities since 1978. This research aims to find out and analyze the influence of the culture of the Organization and discipline of work on performance of employees (Employees of the Division study on HR and the Division General; & Operations at PT PJB UP Gresik). This research is a type of causal research that uses a quantitative approach with a population of 50 people using sampling techniques and sampling of saturated with as many as 50 employees in the sample Division HR Division and the Public; & Operations at PT PJB UP Gresik. The results of this research show that the culture of the organization provide positive and significant influence on employee performance. The discipline of work and significant positive influence on performance of employees.” Keywords: organizational culture, discipline, Employee Performance